2018
DOI: 10.1002/aoc.4220
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insight into the photodeactivation pathway of the tetradentate Pt(II) complex: The π‐conjugation effect

Abstract: In this work, density functional theory and time-dependent density functional theory were used to investigate the effects of π-conjugation of the ligand on the photophysical properties, radiative/nonradiative processes and phosphorescence quantum efficiency of tetradentate cyclometalated Pt (II) complex with carbazolyl-pyridine ligands PtNON. By simulating the absorption spectra and emission wavelengths, increasing the π-conjugation of the ligand could cause the absorption and emission wavelengths to red-shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Based on the crystal structures resolved here, the geometries of all packing patterns in the ground (S 0 ) and excited states (T 1 ) were optimized using the restricted and unrestricted density functional theory methods with the PBE0 functional. The frequency of the optimized geometries was calculated to check that all of the stationary points were either minima. In order to simulate the influence of polarization effects of the crystal environment, the polarizable continuum model (PCM) was also taken into account. , On the basis of the optimized structures, the time-dependent DFT (TD-DFT) method was employed to investigate the vertical emission energies.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the crystal structures resolved here, the geometries of all packing patterns in the ground (S 0 ) and excited states (T 1 ) were optimized using the restricted and unrestricted density functional theory methods with the PBE0 functional. The frequency of the optimized geometries was calculated to check that all of the stationary points were either minima. In order to simulate the influence of polarization effects of the crystal environment, the polarizable continuum model (PCM) was also taken into account. , On the basis of the optimized structures, the time-dependent DFT (TD-DFT) method was employed to investigate the vertical emission energies.…”
Section: Methodsmentioning
confidence: 99%
“…The ZFS of organometallic complexes is dependent not only on the type of the central element of the complexes but also on the chelating scheme, thereby, some Pt­(II) complexes can possess slightly higher values of ZFS . The theoretical estimation of the ZFS value for the representative tetradentate Pt­(II) complex is about 70 cm –1 (ref ). In this regard, we assume applicability of the isotropic averaging scheme for the description of the triplet manifold relaxation in the target tetradentate Pt­(II) complexes and use eqs and in all subsequent calculations.…”
Section: Theorymentioning
confidence: 99%
“…Che et al [10][11][12] reported a series of Pt(II) complex with rigid four-tooth [O^N^C^N] ligands, and they all showed good quantum yield, the highest of which could reach 0.90. The calculation results of Luo et al [13,14] show that π-conjugation can effectively reduce the non-radiation rate constant of the complex. By expanding the π-conjugated system, it is found that the emission wavelength becomes longer and the radiation rate constant decreases.…”
Section: Introductionmentioning
confidence: 98%